1978
DOI: 10.1126/science.200.4345.1044-a
|View full text |Cite
|
Sign up to set email alerts
|

Lancefield Swamp and the Extinction of the Australian Megafauna

Abstract: Excavations into the Australian swamp of Lancefield show that a bone bed dated at 26,000 years ago contains perhaps 10,000 giant extinct animals. Associated artifacts suggest that humans were in the area, but the direct cause of death of the animals is, on present evidence, not explicable. Such a recent date for the classic megafauna shows that it was living together with humans for at least 7000 years in southeast Australia. This enduring association argues against a catastrophic and rapid overkill in the Aus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 4 publications
3
50
0
Order By: Relevance
“…Some authors suggest that climate change may have been the primary cause of the megafaunal extinction (Calaby, 1976 ;Horton, 1977Horton, , 1984Main, 1978 ;Archer, 1984), but this is inconsistent with the megafauna having survived numerous glacial-interglacial cycles thought to have been of similar severity to the last glacial (White & O'Connell, 1979 ;Martin, 1984 ;Wright, 1986 b ;Kershaw, 1989). Although archaeological material has been found associated with megafaunal remains, there is no clear-cut evidence of human predation (Gillespie et al, 1978 ;Archer, 1984 ;Gorecki et al, 1984 ;Dodson et al, 1993 b). In marked contrast to northern hemisphere megafaunal extinctions, no killing grounds and tools designed to kill large animals have been found in Australia (Owen-Smith, 1989).…”
Section: Megafaunal Extinction and Aboriginal Landscape Burning : Mecmentioning
confidence: 99%
“…Some authors suggest that climate change may have been the primary cause of the megafaunal extinction (Calaby, 1976 ;Horton, 1977Horton, , 1984Main, 1978 ;Archer, 1984), but this is inconsistent with the megafauna having survived numerous glacial-interglacial cycles thought to have been of similar severity to the last glacial (White & O'Connell, 1979 ;Martin, 1984 ;Wright, 1986 b ;Kershaw, 1989). Although archaeological material has been found associated with megafaunal remains, there is no clear-cut evidence of human predation (Gillespie et al, 1978 ;Archer, 1984 ;Gorecki et al, 1984 ;Dodson et al, 1993 b). In marked contrast to northern hemisphere megafaunal extinctions, no killing grounds and tools designed to kill large animals have been found in Australia (Owen-Smith, 1989).…”
Section: Megafaunal Extinction and Aboriginal Landscape Burning : Mecmentioning
confidence: 99%
“…In Figure 3, the upper panel shows 14 C and other dates from Lancefield Swamp, a spring site in southeastern Australia with abundant megafauna and sparse archaeology. The megafaunal remains occur in a discrete bone bed 1.5-1.7 m below present surface, underlain by a channel fill from which charcoal was dated to about 30 ka (Gillespie et al 1978). Bones and teeth are very poorly preserved, with extensive mineral replacement (sometimes retaining the fibrous texture of dentine or collagen) but containing little or no residual protein; 14 C dates on bone fractions are widely scattered and unreliable.…”
Section: People and Megafaunamentioning
confidence: 99%
“…For example, apart from one site (Murray et al, 1980), there has been no evidence of extinct species found in the recently unearthed Pleistocene sites of southwestern Tasmania (see below). This appears to be so even where large numbers of extinct fauna have been excavated, for example, at Lancefield (Gillespie et al, 1978). While climate undoubtedly played an influential role (Horton, 1980), extinctions appear to have occurred differentially across the continent; for example, prior to ca.…”
Section: Faunal Extinctionsmentioning
confidence: 95%